STUDY AND IMPROVEMENT OF THE QUALITY OF COMPRESSED AIR TREATMENT IN COMPRESSOR UNITS WITH THE DEVELOPMENT OF A TECHNICAL SOLUTION - Kurbonov O.M; Halimov Z.Sh; Shermanov S.U (Western European Studies, 2024)
Modern production processes are becoming increasingly complex, resulting in an everincreasing rate of growth and the constant improvement of technological equipment. Many important components and units in the production process are pneumatically driven, and compressor equipment is responsible for their operation. Compressed air is one of the most common energy carriers in any industrial plant. And the combination of devices associated with its processing and distribution, including compressors, heat exchangers, cleaning and drying devices, transport and distribution communications, is a rather complex and energy intensive industrial system, whose level of perfection and operation depends on the performance of technological processes where compressed air is used. In this paper we examine the current problems in compressed air treatment in compressor installations
Keywords: air supply; pneumocyclone; centrifugal force; filter